Speeding: a review of self-reported effects of amphetamine-type stimulants (ATS). (2nd January 2020) - Green, Bob; Hayllar, Jeremy; Anderson, Carrick
Abstract: Speeding: A review of self-reported effects of Amphetamine-type Stimulants (ATS). Background: Despite well-publicized adverse effects, Amphetamine-type Stimulants (ATS) continue to be widely used. The self-report of ATS users provides a valuable source of information regarding the diverse range of ATS effects. Examining the self-reported acute effects of ATS users supports a fuller understanding of potential drivers, inhibitors, perceived benefits and negative consequences of ATS use. Method: A systematic review of studies reporting the prevalence of self-reported effects was undertaken. Effects meeting the review criteria were categorised using a computerised dictionary of terms, and their point prevalence estimated. Results: Over half of the MDMA and amphetamine participants reported increased sociability, energy, talkativeness and positive mood. There was a range of psychological and physiological effects commonly reported by MDMA users, not reported by amphetamine users. Almost a third of MDMA users reported hallucinations and 20% paranoia, however, physical violence was not frequently examined or reported. No studies meeting the review criteria were located that described the frequency of self-reported methamphetamine effects. Unlike areas such as alcohol and cannabis where there is an established literature examining drug expectancies, there is limited research into amphetamine or methamphetamine expectancies which impedes a comprehensive understanding of particular effects which reinforce use, especially for recreational users. Conclusions: A wide range of self-reported ATS effects and their prevalence were estimated. The absence of studies documenting self-reported methamphetamine effects and studies on ATS expectancies are notable gaps in the literature.